Coating varnish composition, and plastic film label

JP2025021892AActive Publication Date: 2025-02-14SAKATA INX
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2023125982
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-02
Publication Date
2025-02-14
Estimated Expiration
2043-08-02

AI Technical Summary

Benefits of technology

【0011】 本発明のコーティングニス組成物は、バインダー樹脂、及び溶剤を含有し、さらに、ワックス粒子、前記ワックス粒子以外の樹脂ビーズ、及び脂肪酸アミドを含有し、前記樹脂ビーズは、平均粒子径が4~15μmであり、前記コーティングニス組成物中、0.1質量%以上1.5質量%以下であり、前記脂肪酸アミドは、前記コーティングニス組成物中、0.1質量%以上0.3質量%以下であることから、良好な滑り性を有しながらも分散安定性及び耐泡立ち性が良好であり、さらに、透明性、接着性、耐スクラッチ性、及び耐摩擦性に優れる印刷層が形成できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025021892000001
    Figure 2025021892000001
Patent Text Reader

Abstract

To provide a coating varnish composition which has good dispersion stability and foaming resistance while having good slipperiness, and enables formation of a printed layer excellent in transparency, adhesion, scratch resistance and abrasion resistance.SOLUTION: A coating varnish composition is provided, containing binder resin, and a solvent, and further containing wax particles, resin beads other than the wax particles, and a fatty acid amide, and each of the resin beads has an average particle diameter of 4 to 15 μm. In the coating varnish composition, 0.1 mass% or more and 1.5 mass% or less of the resin beads are contained, and 0.1 mass% or more and 0.3 mass% or less of the fatty acid amide is contained.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a coating varnish composition and a plastic film label. [Background technology]

[0002] Two types of labels are mainly used for PET bottles for soft drinks, etc.: shrink labels and roll labels. Shrink labels are attached to the bottle by applying heat to shrink the label. On the other hand, roll labels are attached by wrapping them around the bottle, so they can be made thinner than shrink labels and have the advantage that they can be easily peeled off by simply pulling the edge of the label. These labels need to have good slip properties in order to be easily attached to the bottle.

[0003] Patent Document 1 describes an ink composition that has good slip properties and is printed on the inner surface (the side that comes into contact with a bottle) of a plastic film label.

[0004] Furthermore, Patent Document 2 describes an ink composition for printing on a substrate such as a plastic film, which contains a specific binder resin, a specific hydrocarbon wax, a fatty acid amide, and a solvent. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2006-16484 A [Patent Document 2] JP 2022-166508 A Summary of the Invention [Problem to be solved by the invention]

[0006] On the other hand, the printing ink composition specifically disclosed in Patent Document 1 had insufficient dispersion stability. In addition, when a printed layer was formed using the ink composition specifically disclosed in Patent Document 2, it had excellent anti-slip properties but poor slip properties, and therefore was insufficient in attaching it to a bottle.

[0007] Furthermore, coating varnish compositions for coating the inner surface of plastic film labels are required to have not only slip properties but also adhesion, scratch resistance, abrasion resistance, and bubbling resistance.

[0008] Therefore, the present invention has been made in consideration of the above-mentioned situation, and aims to provide a coating varnish composition that has good slip properties while also having good dispersion stability and foaming resistance, and can form a printed layer that is excellent in transparency, adhesion, scratch resistance, and abrasion resistance.

[0009] Another object of the present invention is to provide a plastic film label laminated with a printed layer formed from the above coating varnish composition. [Means for solving the problem]

[0010] That is, the present invention comprises the following configuration. [1] A coating varnish composition containing a binder resin and a solvent, and further containing wax particles, resin beads other than the wax particles, and a fatty acid amide, wherein the resin beads have an average particle size of 4 to 15 μm and account for 0.1% by mass or more and 1.5% by mass or less in the coating varnish composition, and the fatty acid amide accounts for 0.1% by mass or more and 0.3% by mass or less in the coating varnish composition. [2] The coating varnish composition according to [1], wherein the binder resin is at least one selected from the group consisting of acrylic resins, polyurethane resins, polyester resins, and cellulose resins. [3] A coating varnish composition according to [1] or [2], wherein the resin beads are acrylic resin beads and / or benzoguanamine resin beads. [4] The coating varnish composition according to any one of [1] to [3], wherein the wax particles have an average particle diameter of 3 to 10 μm. [5] The coating varnish composition according to any one of [1] to [4], which is used for coating the inner surface of a plastic film label. [6] A plastic film label comprising a plastic film and a printed layer formed from the coating varnish composition according to any one of [1] to [5] laminated thereon. Effect of the Invention

[0011] The coating varnish composition of the present invention contains a binder resin and a solvent, and further contains wax particles, resin beads other than the wax particles, and a fatty acid amide, the resin beads having an average particle diameter of 4 to 15 μm and occupying from 0.1% by mass to 1.5% by mass in the coating varnish composition, and the fatty acid amide occupies from 0.1% by mass to 0.3% by mass in the coating varnish composition. Therefore, a printed layer can be formed which has good slip properties while also having good dispersion stability and foaming resistance, and which is also excellent in transparency, adhesion, scratch resistance, and abrasion resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] <Coating varnish composition> The coating varnish composition of the present invention contains a binder resin, wax particles, resin beads other than the wax particles, a fatty acid amide, and a solvent. The coating varnish composition is different from a color ink composition in that it does not substantially contain a pigment as a coloring component. Here, "substantially does not contain" generally means that the pigment is contained in the coating varnish composition in an amount of 0.5% by mass or less, preferably 0.2% by mass or less, and most preferably is not contained.

[0013] <Binder resin> The binder resin is a component that functions as a binding resin for constituting a printed layer formed by the coating varnish composition applied to a substrate. The binder resin is preferably at least one selected from the group consisting of polyurethane resin, cellulose resin, polyester resin, and acrylic resin. The binder resin preferably contains two or more resins, and is preferably a polyurethane resin and a cellulose resin. By using these two resins in combination, the slipperiness of the printed layer formed can be further increased, and the physical properties of the printed layer (varnish film), such as blocking resistance and scratch resistance, can be further improved. The content of the binder resin in the coating varnish composition is preferably 6% by mass or more and 25% by mass or less, and preferably 10% by mass or more and 20% by mass or less.

[0014] The polyurethane resin is a resin having two or more urethane bonds in the molecule, and can be used without any particular limitation. Examples of the polyurethane resin include a polyurethane resin obtained by reacting a diisocyanate compound, a diol compound, a chain extender, and a reaction terminator (obtained by further reacting a chain extender and a reaction terminator with a urethane prepolymer obtained by reacting a diisocyanate compound with a diol compound).

[0015] Examples of the diisocyanate compound include aliphatic diisocyanate compounds such as hexamethylene diisocyanate and 2,2,4-trimethylhexamethylene diisocyanate; alicyclic diisocyanate compounds such as isophorone diisocyanate and hydrogenated xylylene diisocyanate; aromatic aliphatic diisocyanate compounds such as xylylene diisocyanate and α,α,α',α'-tetramethyl xylylene diisocyanate; and aromatic diisocyanate compounds such as toluylene diisocyanate and diphenylmethane diisocyanate. Among these, alicyclic or aromatic aliphatic diisocyanate compounds are preferred, and isophorone diisocyanate and α,α,α',α'-tetramethyl xylylene diisocyanate are particularly preferred, from the viewpoint of easy reaction control and good balance of performance of the resulting polyurethane resin. At least one of the diisocyanate compounds may be used, and two or more of them may be used in combination.

[0016] Examples of the diol compound include polymer diols such as polyester diol compounds, polyether diol compounds, polycarbonate compounds, polybutadiene glycol compounds, etc. At least one diol compound may be used, and two or more diol compounds may be used in combination.

[0017] Examples of the polyester diol compound include those obtained by reacting a low molecular weight diol component (linear glycols such as ethylene glycol, 1,3-propanediol, and 1,4-butanediol; branched glycols such as 1,2-propanediol, neopentyl glycol, 3-methyl-1,5-pentanediol, and 2,4-diethyl-1,5-pentanediol; and ether-based diols such as diethylene glycol and triethylene glycol) with a dicarboxylic acid component (saturated and unsaturated aliphatic dicarboxylic acids such as succinic acid, adipic acid, and maleic acid; and aromatic dicarboxylic acids such as phthalic acid).

[0018] Examples of the polyether diol compound include polyester diol compounds obtained by ring-opening reaction of cyclic ester compounds (lactones, etc.), and polyether diol compounds obtained by polyaddition of oxyalkylenes (ethylene oxide, propylene oxide, etc.) or tetrahydrofuran to diol compounds ((poly)alkylene glycol compounds, bisphenols, etc.).

[0019] From the viewpoint of various physical properties of the ink, the diol compound is preferably a polyester diol or a polyether diol.

[0020] The chain extender can be a compound having two or more functional groups (amino group, hydroxyl group, etc.) that can react with an isocyanate group in the molecule. Examples of compounds having two or more amino groups in the molecule include diamines having two primary amino groups (ethylenediamine, 1,3-propylenediamine, 1,4-butylenediamine, hexamethylenediamine, isophoronediamine, etc.), diamines having one primary amino group and one secondary amino group (2-ethylaminoethylamine, etc.), and polyamines having two primary amino groups and one or more secondary amino groups (diethylenetriamine, triethylenetetramine, etc.). Examples of hydroxyl-containing compounds having two or more hydroxyl groups in the molecule include low molecular weight diols (ethylene glycol, propylene glycol, butylene glycol, diethylene glycol, triethylene glycol, etc.). Further, examples of compounds having two amino groups and one hydroxyl group in the molecule include 1-mol adducts of ethylene oxide to diamines having two primary amino groups such as aminoethylethanolamine and aminopropylethanolamine. At least one of the chain extenders may be used, and two or more of them may be used in combination.

[0021] From the viewpoint of introducing functional groups such as hydroxyl groups and amino groups into the polyurethane resin molecule, the chain extender can be a compound having three or more functional groups such as amino groups and hydroxyl groups. Examples of the compound having three or more functional groups such as amino groups and hydroxyl groups include glycerin and aminoethylethanolamine.

[0022] The reaction terminator may be a compound having one or more functional groups (amino group, hydroxyl group, etc.) capable of reacting with an isocyanate group in the molecule. Specific examples of the reaction terminator include monoalcohols (methanol, ethanol, etc.), monoamines (n-butylamine, di-n-butylamine, etc.), and alkanolamines having one amino group and one hydroxyl group in the molecule (monoethanolamine, ethylethanolamine, diethanolamine). The reaction terminator may also be a compound listed as the chain extender. From the viewpoint of introducing functional groups such as hydroxyl groups and amino groups into the polyurethane resin molecule, the reaction terminator may be an alkanolamine having one amino group and one hydroxyl group in the molecule, or a diamine having two primary amino groups or a low molecular weight diol exemplified as the chain extender. At least one of the reaction terminators may be used, and two or more of them may be used in combination.

[0023] In producing the urethane prepolymer obtained by reacting the diisocyanate compound with the diol compound, the equivalent ratio of NCO of the diisocyanate compound to OH of the diol compound (equivalent of NCO of the diisocyanate compound / equivalent of OH of the diol compound) is preferably 1.3 to 3, and more preferably 1.5 to 2.

[0024] The chain extender is preferably reacted in an amount of about 0.5 to 0.95 equivalents relative to the remaining isocyanate groups of the prepolymer, and the reaction terminator is preferably reacted in an amount of about 2 moles relative to 1 mole of the polyurethane resin after chain extension.

[0025] The weight average molecular weight of the polyurethane resin is preferably 5,000 to 50,000, more preferably 10,000 to 30,000. The weight average molecular weight of the present invention can be measured by gel permeation chromatography (GPC). As an example, chromatography is performed using a Water2690 (manufactured by Waters) as a GPC device and a PLgel, 5μ, MIXED-D (manufactured by Polymer Laboratories) as a column under the conditions of tetrahydrofuran as a developing solvent, a column temperature of 25°C, a flow rate of 1 milliliter / minute, an RI detector, a sample injection concentration of 10 milligrams / milliliter, and an injection amount of 100 microliters, and the weight average molecular weight can be calculated as a polystyrene-equivalent weight average molecular weight.

[0026] The polyurethane resin is preferably a polyurethane resin having a functional group such as a hydroxyl group or an amino group. As a method for obtaining a polyurethane resin having such a functional group, a known method can be adopted, such as a method using a compound having three or more functional groups such as the amino group or the hydroxyl group as a chain extender, or a method of reacting the diisocyanate compound at a molar ratio less than 1.0 times that of the diol compound without using the chain extender or the reaction terminator. When the polyurethane resin has an amino group, the amine value is preferably in the range of 0.1 to 10 mgKOH / g. The amine value means the amine value per 1 g of solid content, and can be measured by using a 0.1 N hydrochloric acid aqueous solution and measuring by potentiometric titration (for example, COMTITE (AUTO TITRATOR COM-900, BURET B-900, TITSTATIONK-900), manufactured by Hiranuma Sangyo Co., Ltd.), and then converting it into the equivalent amount of potassium hydroxide.

[0027] Examples of the cellulose resin include cellulose ester resins such as cellulose acetate propionate and cellulose acetate butyrate; nitrocellulose; hydroxyalkyl cellulose; and carboxyalkyl cellulose. The cellulose ester resin preferably has an alkyl group such as a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, a pentyl group, and a hexyl group. The cellulose resin is preferably cellulose acetate propionate, cellulose acetate butyrate, and nitrocellulose (nitrocellulose), and more preferably nitrocellulose (nitrocellulose). The weight-average molecular weight of the cellulose resin is preferably 5,000 to 200,000, and more preferably 10,000 to 50,000.

[0028] Nitrocellulose is usually obtained by reacting native cellulose with nitric acid, and is a nitric acid ester in which three hydroxyl groups in the native cellulose are replaced with nitric acid groups. The average degree of polymerization of nitrocellulose is preferably 20 to 200, more preferably 30 to 150. The nitrogen content of nitrocellulose is usually about 10.5 to 12.5 mass%.

[0029] <Wax particles> The coating varnish composition contains the wax particles, which improves scratch resistance and abrasion resistance. As the wax particles, a hydrocarbon wax can be used, such as polyethylene wax, polypropylene wax, Fischer-Tropsch wax, carnauba wax, paraffin wax, and microstearate wax. The wax particles can be used alone or in combination of two or more kinds. From the viewpoint of scratch resistance and printability, the average particle size of the wax particles is preferably 3 μm or more and 10 μm or less. The average particle size of the wax particles is the cumulative 50% particle size (median size (D50)) on a volume basis measured by a laser diffraction / light scattering method.

[0030] The amount of the wax particles in the coating varnish composition is preferably 0.1% by mass or more and 1.0% by mass or less, and more preferably 0.15% by mass or more and 0.5% by mass or less.

[0031] <Resin beads> The resin beads are resin beads other than the wax particles, and have an average particle diameter of 4 to 15 μm. The coating varnish composition contains the resin beads, which improves the slipperiness. Examples of the resin beads include acrylic resin beads, benzoguanamine resin beads, melamine resin beads, and silicon resin beads. Among these, acrylic resin beads and benzoguanamine resin beads are preferred. The resin beads can be used alone or in combination of two or more. The average particle diameter of the resin beads is preferably 4 μm or more from the viewpoints of transparency and slipperiness, and is preferably 15 μm or less from the viewpoints of scratch resistance and abrasion resistance. The average particle diameter of the resin beads is the cumulative 50% particle diameter (median diameter (D50)) based on volume measured by a laser diffraction / light scattering method.

[0032] The content of the resin beads in the coating varnish composition is 0.1% by mass or more and 1.5% by mass or less. From the viewpoint of improving slipperiness, the content of the resin beads in the coating varnish composition is preferably 0.3% by mass or more, and from the viewpoint of improving transparency, the content of the resin beads is preferably 1.2% by mass or less.

[0033] <Fatty acid amide> The coating varnish composition contains the fatty acid amide, and thus the dispersion stability is improved. Examples of the fatty acid amide include saturated fatty acid amide, unsaturated fatty acid amide, modified fatty acid amide, etc. The fatty acid amide may be used alone or in combination of two or more kinds.

[0034] The amount of the fatty acid amide in the coating varnish composition is 0.1% by mass or more and 0.3% by mass or less. From the viewpoint of improving the dispersion stability, the amount of the fatty acid amide in the coating varnish composition is preferably 0.15% by mass or more, and from the viewpoint of improving the foaming resistance, the amount of the fatty acid amide in the coating varnish composition is preferably 0.25% by mass or less.

[0035] <Solvent> The solvent of the present invention may be any known organic solvent without any particular limitation, but from the viewpoint of environmental consideration, it is preferable that the solvent does not contain an aromatic hydrocarbon-based organic solvent. Examples of such solvents include alcohol-based organic solvents such as methanol, ethanol, n-propanol, isopropanol, butanol, ketone-based organic solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, ester-based organic solvents such as methyl acetate, ethyl acetate, propyl acetate, butyl acetate, aliphatic hydrocarbon-based organic solvents such as n-hexane, n-heptane, n-octane, and alicyclic hydrocarbon-based organic solvents such as cyclohexane, methylcyclohexane, ethylcyclohexane, cycloheptane, and cyclooctane. At least one of the solvents may be used, and two or more of them may be used in combination, taking into consideration the solubility and drying properties of the binder resin. However, from the viewpoint of environmental consideration, it is preferable to suppress the use of ketone-based organic solvents among the solvents.

[0036] The content of the solvent in the coating varnish composition is preferably 65% ​​by mass or more and 90% by mass or less, and more preferably 70% by mass or more and 85% by mass or less.

[0037] The coating varnish composition may contain any of a leveling agent, a surfactant, a thickener, an antioxidant, an antifoaming agent, a plasticizer, a metal chelate crosslinking agent, a hardener, an antistatic agent, and the like, as long as the performance of the composition is not impaired.

[0038] The total amount of the binder resin, the wax particles, the resin beads other than the wax particles, the fatty acid amide, and the solvent in the coating varnish composition is preferably 70 mass% or more, more preferably 80 mass% or more, and even more preferably 85 mass% or more.

[0039] The method for preparing the coating varnish composition is not particularly limited, and for example, the above-mentioned components may be added in order or simultaneously, and prepared using a roll mill, kneader, high-speed mixer, bead mill, ball mill, sand mill, ultrasonic disperser, high-pressure disperser, or the like.

[0040] The coating varnish composition of the present invention can be applied (printed) to a plastic film and dried to form a varnish layer (printed film). As the support film, a film generally used as a printing material can be used, but from the viewpoint of use in a plastic film label, films such as polyethylene terephthalate and polyolefin are preferred. In addition, at least one surface of the plastic film may be provided with an ink layer (printed film) on which characters, images, etc. are printed. The printing method is preferably gravure printing. Conventionally known conditions can be appropriately adopted as printing conditions in the printing, and in this case, the coating varnish composition is preferably diluted with the solvent so as to have an appropriate viscosity according to the printing conditions. EXAMPLES

[0041] The present invention will be described below with reference to examples, but the present invention is not limited to these.

[0042] <Synthesis Example 1> <Production of polyurethane resin> In a four-neck flask equipped with a stirrer, a cooling tube, and a nitrogen gas inlet tube, 200 parts by mass of 3-methyl-1,5-pentylene adipate diol having a number average molecular weight of 2000 and 44.4 parts by mass of isophorone diisocyanate were charged, and the mixture was reacted at 100 to 105 ° C. for 6 hours while introducing nitrogen gas. The mixture was allowed to cool to near room temperature, and 486 parts by mass of propyl acetate and 122 parts by mass of isopropanol were added, followed by adding 13.6 parts by mass of isophorone diamine to carry out a chain extension reaction, and then adding 2.4 parts by mass of ethylene diamine to terminate the reaction, thereby obtaining a polyurethane resin varnish PU1 (solid content 30%, weight average molecular weight of polyurethane resin 16,000, functional group capable of reacting with an isocyanate group contained in the molecule = primary amino group, amine value 6).

[0043] <Examples 1-7, Comparative Examples 1-7> <Preparation of Coating Varnish Composition> The materials were mixed in the proportions (parts by mass) shown in Table 1 to prepare each coating varnish composition.

[0044] The following evaluations were carried out using each of the coating varnish compositions obtained above. The pass criteria for each evaluation was "good" or "good", with "good" being more preferable. The results are shown in Table 1.

[0045] <Dispersion stability> Each coating varnish composition was placed in a sealed container and left to stand at 40° C. for 7 days, after which the state of settling was visually inspected and evaluated according to the following evaluation criteria. ○: No sediment △: A small amount of sediment is present ×: A lot of sedimentation

[0046] <Foaming resistance> Each coating varnish composition was mixed with a dilution solvent (ethyl acetate / propyl acetate / isopropyl alcohol = 50 / 25 / 25) in a mass ratio of 2:1 to give a diluted varnish. The varnish was then run on a gravure press at a speed of 200 m / min for 60 minutes while the engine was idle. The foaming was then visually evaluated according to the following criteria: ○: No bubbles in the ink pan △: A small amount of foaming occurs in the ink pan. ×: A large amount of foaming occurs in the ink pan.

[0047] <Creating evaluation pieces> Each coating varnish composition was applied to an OPP foam (P2161, 25 μm, manufactured by Toyobo Co., Ltd.) using a bar coater (φ0.1 mm) and dried to prepare an evaluation piece.

[0048] <Slipperiness> The varnished surface of each evaluation piece prepared above was overlapped with the PET film and left to stand for 10 seconds, then slid at a sliding speed of 500 mm / min to measure the static and dynamic friction coefficients in accordance with JIS-K7125 and evaluate them according to the evaluation criteria shown below. ◯: Both the static and dynamic friction coefficients are in the range of 0.1 to 0.5. ×:Other than the above

[0049] <Haze> Each of the evaluation pieces prepared above was visually observed and evaluated according to the following evaluation criteria. 〇: The transparency of the base material is maintained △: Slight whitening is observed ×: Clearly bleached

[0050] <Adhesiveness> Cellophane tape was applied to the printed surface of each evaluation piece prepared above, and the tape was then quickly peeled off, and the degree of peeling of the varnish coating was evaluated according to the following evaluation criteria. ◎: The varnish coating area ratio was such that there was absolutely no peeling from the film. ○: Peeling from the film was greater than 0% and less than 5% of the area of ​​the varnish coating. △: 5% or more but less than 30% of the area of ​​the varnish coating peeled off from the film ×: 30% or more of the area of ​​the varnish coating peeled off from the film.

[0051] <Scratch resistance> The printed surface of each evaluation piece prepared above was rubbed strongly with the back of a fingernail, and the degree of peeling of the varnish coating was evaluated according to the evaluation criteria shown below. 〇: No scratches or peeling at all △: Partially peeled off ×: Most of the surface peeled off or completely peeled off

[0052] <Abrasion resistance> The printed surface of each evaluation piece created above was rubbed back and forth 100 times with a load of 200g using a Gakushin testing machine (manufactured by Daiei Scientific Instruments Manufacturing Co., Ltd.) using a K-liner as the friction element, and the degree to which the varnish coating fell off was evaluated according to the evaluation criteria shown below. ◎: No varnish coating peeling off ○: More than 0% but less than 10% of the varnish film falls off △: 10% to less than 50% of the varnish coating falls off ×: 50% or more of the varnish coating has fallen off.

[0053] [Table 1]

[0054] In Table 1, PU1 is polyurethane resin varnish (Synthesis Example 1, solid content 30%); CAP-482-0.5 is a cellulose resin (manufactured by EASTMAN CHEMICAL); MR-1HG is acrylic resin beads (average particle size 1 μm, manufactured by Soken Chemical Engineering Co., Ltd.); Eposter M05 is benzoguanamine resin beads (average particle size 5 μm, Nippon Shokubai Co., Ltd.); MR-10HG is acrylic resin beads (average particle size 10 μm, manufactured by Soken Chemical Industries, Ltd.); Techpolymer MBX-20 is an acrylic resin bead (average particle size 20 μm, manufactured by Sekisui Plastics Co., Ltd.); Polycon PA-60 is a polyethylene wax (average particle size 6 μm, manufactured by Polycon Corporation, active ingredient 26%); CERIDUST3610 is a polyethylene wax (average particle size 4.5-5.5 μm, Clariant Chemicals); CERIDUST3620 is a polyethylene wax (average particle size 7.5-9.5 μm, Clariant Chemicals); Disparlon PFA-220 is a fatty acid amide (Kusumoto Chemicals, 20% active ingredient); Lamiol R hardener refers to a hardener (isocyanate compound, manufactured by Sakata Inx Corporation).

Claims

1. A coating varnish composition containing a binder resin and a solvent, Further, the composition contains wax particles, resin beads other than the wax particles, and a fatty acid amide, The resin beads have an average particle size of 4 to 15 μm and are present in the coating varnish composition at a content of 0.1% by mass or more and 1.5% by mass or less. A coating varnish composition, characterized in that the fatty acid amide is contained in an amount of 0.1 mass % or more and 0.3 mass % or less in the coating varnish composition.

2. 2. The coating varnish composition according to claim 1, wherein the binder resin is at least one selected from the group consisting of an acrylic resin, a polyurethane resin, a polyester resin, and a cellulose resin.

3. 3. The coating varnish composition according to claim 1, wherein the resin beads are acrylic resin beads and / or benzoguanamine resin beads.

4. 3. The coating varnish composition according to claim 1, wherein the wax particles have an average particle size of 3 to 10 μm.

5. 3. The coating varnish composition according to claim 1, which is used for coating the inner surface of a plastic film label.

6. A plastic film label comprising a plastic film and a printed layer formed from the coating varnish composition according to claim 1 or 2 laminated thereon.

Citation Information

Patent Citations

  • Coating composition and production thereof

    JP1982008260A

  • Coating composition for plastic film

    JP1998513218A

  • Packaging container

    JP2001328613A

  • Reflective coating for spray coating

    JP2002012829A

  • Cylindrical shrink label, container with label, and coating agent for shrink label

    JP2006349749A